The association between intolerance of uncertainty and academic burnout among university students: the role of self-regulatory fatigue and self-compassion - Qiang, Jingyu; He, Xiaowen; Xia, Zheng; Huang, Jing; Xu, Cheng (Frontiers in Public Health, 2024)
Introduction Increased uncertainty is a major feature of the current society that poses significant challenges to university students' mental health and academics. However, current research has not paid sufficient attention to this issue, and no study has explored the underlying mechanisms between intolerance of uncertainty and academic burnout among university students. Methods This study examined the association between uncertainty intolerance and academic burnout among university students and the role of self-regulatory fatigue and self-compassion in light of the theory of limited resources. Convenience sampling was used to survey 1,022 Chinese university students. Results The findings demonstrated that intolerance of uncertainty significantly influenced university students' academic burnout with self-regulatory fatigue serving as a key mediator. Additionally, self-compassion can effectively moderate the effects of intolerance of uncertainty on self-regulatory fatigue and academic burnout. Discussion These results indicated that the depletion of cognitive resources brought about by uncertainty in the current highly uncertain social environment may be one of the key pathways to academic burnout among university students. Furthermore, current research provides insights into how to mitigate the negative effects of uncertainty on university students.